(untitled) (Revista de Estudos da Linguagem, 2024)
This article discusses the possibilities for building Kimbundu-Portuguese-Kimbundu bilingual corpora in order to studying language contact phenomena between these two languages. An approximation is made between the areas of Corpus Linguistics and African Linguistics, emphasizing the case of linguistic contact in the corpora in sight. It is argued that Kimbundu and Portuguese have a historical relation that allows the elaboration of written corpus based on the documents of its descriptive tradition that started in the 17th century and a spoken corpus resulting from recent research projects that deal with vernacular varieties of Portuguese and its relation to the African language of this study. To this end, we sought to study the state of the art of the description of Kimbundu and Portuguese in Angola in order to demonstrate the need and feasibility of building bilingual written and spoken Kimbundu-Portuguese-Kimbundu corpora. It is hoped that the production of these bilingual corpora may contribute to the knowledge of the situation of contact between both Angolan languages under study, based on empirical material necessary to understand the real situation of contact between these languages of Angola besides to support hypothesis about an Afro-Brazilian continuum of Portuguese.